2011
DOI: 10.1007/s10333-011-0282-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of agricultural ecosystem services in fallowing land based on farmers’ participation and model simulation

Abstract: Fallowing with green fertilizer can benefit agricultural ecosystem services (AES). Farmers in Taiwan do not implement fallow practices and plant green fertilizer because the current subsidy level (46,000 NT$ per ha) is too low to manage fallowing. This paper defines the objective of government agriculture policy or the farmer's objective as maximization of farm productivity, approximated to the value of social welfare and AES. Farms, which do not follow proper fallowing practices, often have poorly maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although several studies have shown significant weed seed predation by rodents (Westerman et al 2003a ; Daedlow et al 2013 ; Fischer et al 2017 ), the general perception of rodents as crop pests is common in the scientific literature (Brown et al 2007 ; Liu et al 2012 ; Hauck et al 2014 ). Compared to birds, rodents have received less attention as service providers.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown significant weed seed predation by rodents (Westerman et al 2003a ; Daedlow et al 2013 ; Fischer et al 2017 ), the general perception of rodents as crop pests is common in the scientific literature (Brown et al 2007 ; Liu et al 2012 ; Hauck et al 2014 ). Compared to birds, rodents have received less attention as service providers.…”
Section: Discussionmentioning
confidence: 99%
“…Indiscriminate ploughing, residue removal/burning, unbalanced use of chemical fertilizers and extractive farming exacerbated the deterioration of soil and atmosphere quality ( Montgomery, 2007 ), soil organic carbon (SOC) pool, soil biodiversity, compaction, increased runoff, accelerated erosion loss of nutrients, carbon and water from the ecosystem, loss of soil resilience and decrease in ecosystem services ( Lal, 2015 ). Therefore, adoption of the balanced cropping practices, such as conservation tillage ( Zhang et al, 2015 ), recycling of crop residues (CRs) ( Devi et al, 2017 ), application of manure ( Tadesse et al, 2013 ) and farmland fallow ( Liu et al, 2012 ), would be much sought after in the present circumstances for improving the soil quality, ecosystem function and yield sustainability of RWCS. Conversion of conventional agricultural practices to conservation has great potential for increasing the soil quality through the presence of C substrate, increasing soil biodiversity, MBC, soil aggregation and improving water and nutrient use efficiency ( Tisdall and Oades, 1982 ; Ghosh et al, 2015 ; Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Biophysical and ecological models capture different processes and functions that control the availability of ESS and is another popular method, with nine of our review papers discussing it [19,24,[26][27][28][29][30][31][32] The most commonly used biophysical and ecological models that can be relevant in agriculture are: soil erosion models like the Universal Soil Loss Equation (USLE) model [38], species distribution models [39], linear programming models [40], and state and transition models [29]. All contribute to an understanding of the ecological and biophysical functions for provisioning and regulating ESS.…”
Section: Biophysical and Ecological Modellingmentioning
confidence: 99%